Taxation of land and economic growth - Shulu Che; Ronald Ravinesh Kumar; Peter Stauvermann (Economies, 2021)
In this paper, we theoretically analyze the effects of three types of land taxes on economic growth using an overlapping generation model in which land can be used for production or consumption (housing) purposes. Based on the analyses in which land is used as a factor of production, we can confirm that the taxation of land will lead to an increase in the growth rate of the economy. Particularly, we show that the introduction of a tax on land rents, a tax on the value of land or a stamp duty will cause the net price of land to decline. Further, we show that the nationalization of land and the redistribution of the land rents to the young generation will maximize the growth rate of the economy.
Keywords: 330; endogenous growth; land property; land rents; overlapping generation model; taxation of land